Analysis of Factors that Influence Interest in Buying Counterfeit Products among West Kalimantan Students through Social Cognitive Theory - Sujani, Dominika; Hari Kristianto, Aloysius (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to determine the influence of self-efficacy on interest in buying counterfeit products, outcome expectancy on interest in buying counterfeit products , social influence on interest in buying counterfeit products. The method used is quantitative with a survey approach. In this study, the population was students from West Kalimantan with a sample of 200 respondents. The data analysis method uses SEM. The results of this study indicate that self-efficacy has a positive but not significant effect on interest in purchasing counterfeit products . Meanwhile, outcome expectancy and social influence have a positive and significant effect on interest in purchasing counterfeit products. In conclusion, outcome expectancy and social influence influence students' buying interest in counterfeit products. In this case, students believe that counterfeit products can provide the same benefits as genuine products. Meanwhile, high self-efficacy or confidence in one's ability to buy counterfeit products tends to show great interest in purchasing counterfeit products . However, the influence of positive self-efficacy on intention to purchase counterfeit products is not always significant, indicating that other factors may be more dominant in influencing purchasing decisions such as perceived usefulness, price and quality of the product purchased